Mass-independent fractionation of oxygen isotopes during high-temperature condensation in cosmochemical plasmas - Nathan Asset; Marc Chaussidon; Guillaume Lombardi; Johan Villeneuve; Romain Tartèse; Smail Mostefaoui; François Robert (Proceedings of the National Academy of Sciences, 2025)
Contrary to all terrestrial rocks, planets and meteorites exhibit oxygen isotope variations decorrelated with the mass difference of their atomic nuclei. It has been proposed that, in the protosolar nebula (PSN), these variations could result from mass independent isotopic fractionation (MIF) either during specific chemical reactions similar to those responsible for the formation of ozone in the Earth’s atmosphere or during ultraviolet (UV)-photolysis of carbon monoxide (CO) gas in the PSN. However, these potential chemical MIF reactions (Chem-MIFs) are not identified in conditions close to the PSN, and there is no experimental demonstration that large MIF signature can be transferred to solids forming in the PSN. Here, we show that MIFs, up to 60‰ depletion in 16 O, are produced by high-temperature reactions in a plasma during the condensation of carbonaceous solids from a gas containing two of the most abundant PSN molecular species (H 2 O and CH 4 ). This effect is attributed to the formation in the plasma of the activated complex H 2 O 2 * followed by its stabilization by reactions with CH x • radicals. Although it is premature to assert that this reaction represents the main process resulting in MIF of oxygen isotopes in the solar system, our result demonstrates the potential importance of a Chem-MIF effect in a PSN where plasma zones develop.